Stockholder Reactions To Departures and Appointments of Key Executives Attributable To Firings - Worrell, Dan L.; Davidson, Wallace N.; Glascock, John L. (Academy of Management Journal, 1993)
This study investigated investors' reactions to announcements of the firings of key executives made over the 25-year period 1963?1987. We found announcements containing information about permanent replacements to he associated with positive market reactions, whereas other types of firing announcements resulted in no market response. In addition, outsider appointments were perceived as beneficial immediately, while insider appointments elicited a wait-and-see reaction.